On the maximal unipotent subgroups of a special linear group over commutative ring - Tylyshchak, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 512.64 We prove that all maximal unipotent subgroups of a special linear group over commutative ring with identity (such that the factor ring of its modulo primitive radical is a finite direct sum of Bezout domains) are pairwise conjugated and describe one maximal unipotent subgroup of the general linear group (and of a special linear group) over an arbitrary commutative ring with identity.